The Concept of Translational Research and School Nursing - Huri Yoğurtçu; Şeyda Özbıçakçı (Dokuz Eylul University, 2021)
The concept of translationality is the result of all the Works and processes that are taken from the theory status of the scientific in formation obtained through research and converted in to practice. Clearly, when the information used in the literature and the application fields is compared, the evidence cannot be converted into practice at the desired level. However, every information that has remained at the level of theory means wasted workforce, finance and ineffective information management. School health nursing requires a high level of use of evidence and translational research. School nursing requires a high level of use of evidence and translational research. The aim of this review is to create a source of information on translational research, to raise awareness of the members of the profession, to contribute to the integration of scientific knowledge to school health nursing and other fields of practice.